The Role of Expert Evidence in the Defence of Provocation and Emotional Stress in South Africa - Sandhya Maharaj (Obiter, 2019)
The provocation defence has emerged as one of the most contentious defences in modern times and has remained that way for many years in jurisdictions such as South Africa, England and Canada. In South Africa, the courts have struggled in deciding what role, if any, provocation should occupy in criminal law. This dynamic approach arises from the psychological or principle-based approach to criminal liability. Provocation and emotional stress are powerful emotions. In South Africa, the criminal law recognises that these emotions may impact criminal liability by causing a temporary loss of criminal capacity. The three notorious acquittals in S v Nursingh, S v Arnold and S v Moses created controversy for the defence. In an attempt to bring clarity to this area of the law and to calm public outrage the court in Eadie effected fundamental changes in the form of a policy brake on the principles underpinning the defence. Unfortunately, this brought more confusion to the defence. However, it is submitted that the uncertain role of expert evidence in relation to this defence has arguably been a source of the problems encountered in the application of this defence. A measure of uncertainty exists regarding what, if any, the role of expert evidence plays in cases involving non-pathological incapacity due to provocation. Reform and development is needed to formulate a new approach not only to provide clarity but also to ensure improved functioning of the defence. The rules governing expert opinion evidence in respect of the defence of non-pathological incapacity are in need of review and legislative intervention.